Serum level of Interleukin (IL)-8, Monocyte Chemoattractant Protein (MCP)-1 and Tumor Necrosis Factor (TNF)-α in children infected with Entamoeba histolytica - Huda Muneer Ahmed; Fatima Shihab Al-Nasiri (Tikrit Journal of Pure Science)
Entamoeba histolytica is an enteric protozoan parasite which caused tissue invasive amoebiasis. It can induce the production of cytokines (such as IL-8 and TNF-α) and chemokines (such as MCP-1) from intestinal epithelial cells. This study was done to detect the serum level of IL-8, MCP-1 and TNF-α, using an enzyme-linked immunosorbent assay, in 60 children affected by amoebiasis to correlate the production of these cytokines with infection and comparison with the healthy persons (n= 30). Three aged groups (1 month- 2 year, 2-4 year and 4-6 year) were entered in the study for patients and healthy controls. The level of IL-8 (37.22 ± 7.06, 37.35 ± 1.981 and 36.45 ± 4.39 pg/ml) in children with amoebiasis were higher significantly compared with the level in healthy children (29.95 ± 4.30, 26.90 ± 4.17 and 25.32 ± 2.31 pg/ml) in all age groups (1 month- 2 year, 2-4 year and 4-6 year, respectively). Significant differences in the level of MCP-1 which were higher (28.92 ± 1.48, 30.85 ± 3.78 and 31.91 ± 6.82 pg/ml) in children with amoebiasis than in healthy children (18.44 ± 0.74, 22.62 ± 6.25 and 18.30 ± 1.43 pg/ml) in all age groups (respectively). Also, the level of TNF-α were higher significantly (58.05 ± 6.90, 55.87 ± 3.81 and 57.32 ± 8.86 pg/ml) in children with amoebiasis compared with healthy children (42.91 ± 2.54, 43.54 ± 3.42 and 42.64 ± 3.47 pg/ml, respectively) in all age groups (respectively). These findings reflect a role of IL-8, MCP-1 and TNF-α in E. histolytica infection.